(untitled) (Journal of NELTA, 2021)
This study explored woman English as a Foreign Language teachers’ perceptions and practice of professional development. In this research, semi-structured interviews were used for data collection from purposefully selected participants. The participants were three secondary level woman English language teachers of Rupandehi district, state no. 5, Nepal. These teachers had a proper understanding of professional development and were found to put significant personal eﬀort into their professionalism including the training given by the Ministry of Education. In this study, I used the theory of Liberal Feminism. Jaggar (1983) advocates that society as whole benefits from the public contributions of woman in general and educated woman in particular. The study contributes to all concerned stake holders including, teachers, students, teaching institutions, training centers and associations, and trainers to understand the value of professional development for woman EFL teachers, plan and provide more opportunities, and take it into the main stream of ELT discourse to improve the status of woman English language teachers in academia in Nepal.